Asuhan Keperawatan Gerontik Pada Pasien Osteoarthritis di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Shimby Parastian Gusna; Armaita Armaita; Sandra Dewi; Hasmita Hasmita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Osteoarthritis based on WHO in 2020, the number of elderly populations every year will increase. In 2020 the elderly population was around 142 million people then in 2021 it increased to 761 million people, and this number is even expected to increase 2-fold. (OA) is the most common joint disease in adults to old age worldwide. Osteoarthritis ranks 6th out of 14 diseases in the Tresna Werdha Sabai Nan Aluih Sicincin social home in 2025. The purpose of the study is to be able to provide Nursing Care to the elderly with Osteoarthritis at the Tresna Werdha Sabai Nan Aluih Sicincin Social Home in Padang Pariaman Regency including, assessment, diagnosis, intervention, implementation, evaluation, and documentation. The study used a case study research method with a sample used one patient. The study was conducted from February 27 to March 4, 2026. The results of the research on nursing problems found in Mrs. A: Chronic pain related to chronic musculoskeletal conditions, risk of injury characterized by changes in cognitive function, and knowledge deficit related to the client’s lack of knowledge about their illness. After 5 days of implementation and evaluation, the nursing issues of chronic pain, risk of injury, and knowledge deficit were partially resolved. It is hoped that the elderly and caregivers at the home will continue independent interventions and prevent symptoms of the disease, as well as routine health checks at the home’s clinic